On Reducibility of Systems of Linear Differential Equations with Quasiperiodic Skew-Adjoint Matrices - Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove that there exists an open set of irreducible systems in the space of systems of linear differential equations with quasiperiodic skew-adjoint matrices and fixed frequency module.